Structure and deformation history of Astypalea island, Aegean Sea - RING, U. (Bulletin of the Geological Society of Greece, 2001)
Astypalea Island lies south of the Late Cretaceous to Eocene high-pressure belt of the Cyclades and north of the Miocene high-pressure belt of the External Hellenides. The rocks of the island belong to the Tripolitza unit. The latter unit occupies a critical tectonic position in Astypalea between the unmetamorphosed Tripolitza rocks in Crete and the high-pressure Basal unit, which is correlated to the Tripolitza unit, in the Cyclades. We have subdivided the deformation history of Astypalea Island into four events, D; through D4. The problem with interpreting the structural data is that the Di and D2 events cannot unequivocally be ascribed to horizontal crustal contraction or crustal shortening. In our interpretation, Dt caused top-S internal imbrication within the Tripolitza unit as a result of crustal shortening. We envision that this event occurred when the Phyllite-Quartzite and Plattenkalk units were underthrust beneath the Tripolitza unit in the Oligocene. D was probably associated with top-N extension and may be related to large-scale crustal extension across the Cretan detachment in the Early Miocene. D3 caused high-angle faulting due to E-W contraction and D4 was due to N-S extension.